Localized waveguide formation in germanosilicate fiber transmitting femtosecond IR pulses - Tu, Haohua (2008)
Transmission of intense femtosecond 825 nm pulses progressively produces a waveguide at the entrance of a heavily Ge-doped silicate fiber. The waveguide behaves as a multimillimeter long-fiber bandpass filter that scatters away light with wavelengths shorter or longer than 850 nm. This phenomenon has been correlated with the ~800 nm photosensitivity producing type I-IR fiber Bragg gratings in side-written lightly Ge-doped silicate fibers and low-loss waveguides in pure silica bulk glass. A model incorporating color center formation is proposed to understand the underlying mechanism.